Bone morphogenetic protein 2 is a depot-specific regulator of human adipogenesis - Denton, N; Eghleilib, M; Al-Sharifi, S; Todorčević, M; Neville, M; Loh, N; Drakesmith, A; Karpe, F; Pinnick, K (Springer Nature, 2019)
Background: Bone morphogenetic proteins (BMPs) regulate adipogenesis but it is not clear whether they influence regional adipose tissue (AT) development in humans.